Interaction between Fluoxetine and Risperidone and Its Association with Clinical Outcomes in Schizophrenic Patients - Rachmaini, Fitri; Ayu Juwita, Dian; Abdillah, Rahmad; Dwi Afrianti, Rezy; Sri Wahyuni, Fatma (Pharmaceutical Sciences and Research, 2023)
The concurrent use of fluoxetine and risperidone to treat schizophrenia may result in drug interactions. This study aims to analyse the clinical outcomes of fluoxetine-risperidone therapy and the possibility of their interaction in schizophrenic patients. The clinical outcomes are patient status at the time of hospital discharge, the length of hospitalisation and the Positive and Negative Syndrome Scale- Excitement Component (PANSS-EC). This study was conducted prospectively in psychiatric ward of HB Saanin Mental Hospital from May to October 2021 and study subjects were selected using consecutive sampling technique with inclusion criteria. Forty-three patients were eligible for this study. Research data were collected from direct observation and notes from medical records. To provide an overview of the frequency distribution and percentage of the variables evaluated, the data were analysed through descriptive statistics and a chi-square test using SPSS v.22. Symptoms due to risperidone-fluoxetine interaction were found in four patients (10%). The symptoms experienced are categorised as extrapyramidal syndrome (EPS). The results of the clinical outcomes showed that 38 patients (88%) having recovered and five patients (12%) were in remission. The PANSS-EC in male patient (6.24±1.12) was higher than female (5.88±1.12). The length of hospitalization was higher in patient with age 36-45 years (23.72). This study showed no significant relationship between fluoxetine-risperidone interaction on the outcome of therapy (p>0.05). It can be concluded that EPS was found in 10% of schizophrenic patients. However, there was no significant association between EPS due to fluoxetine-risperidone interaction with clinical outcomes.